2009
DOI: 10.1021/ie801674e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation of Gas Hydrate Formation in a Three-Phase Slurry Reactor

Abstract: A dynamic hydrate formation model that incorporates growth kinetics as well as system hydrodynamics and interphase heat and mass transfer rates is presented. Supersaturation ratios and gas consumption rates were evaluated as a function of time for different gas and liquid superficial velocities. The effects of temperature and pressure were also investigated based on available kinetic information in the literature. Finally, the influence of interphase mass transfer resistance relative to kinetic resistance was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Thus, even though gas hydrate crystallization is able to capture CO 2 and enhanced gas/water contact improves the rate of crystallization the contact mode must be such that far less energy is consumed. Some of the potential contact modes are to employ a fixed column using silica sand or silica gel as a medium (Adeyemo et al, in press;Linga, 2009;Seo et al, 2005), a fluidized bed column (Hashemi, 2009) or a non-stirred batch reactor in the presence of cyclopentane as a promoter (Zhang and Lee, 2009). Recently, Adeyemo et al (in press) reported water to hydrate conversions of up to 45% after 4 h of hydrate formation conducted in a fixed bed column with silica gel as a medium for both post-and precombustion capture of CO 2 via hydrate crystallization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, even though gas hydrate crystallization is able to capture CO 2 and enhanced gas/water contact improves the rate of crystallization the contact mode must be such that far less energy is consumed. Some of the potential contact modes are to employ a fixed column using silica sand or silica gel as a medium (Adeyemo et al, in press;Linga, 2009;Seo et al, 2005), a fluidized bed column (Hashemi, 2009) or a non-stirred batch reactor in the presence of cyclopentane as a promoter (Zhang and Lee, 2009). Recently, Adeyemo et al (in press) reported water to hydrate conversions of up to 45% after 4 h of hydrate formation conducted in a fixed bed column with silica gel as a medium for both post-and precombustion capture of CO 2 via hydrate crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…Mori (2003) reviewed the subject and concluded that there is a need to focus on developing hydrate reactors with much improved hydrate forming efficiencies. One of the new approaches underway to enhance the kinetics of hydrate formation is to employ a fixed bed column with silica gel as a medium to capture CO 2 from flue and fuel gases via hydrate crystallization (Adeyemo et al, in press;Seo et al, 2005) or to employ a slurry bubble column (fluidized bed) arrangement to enhance the rate of hydrate formation (Hashemi, 2009) or use a non-stirred batch reactor with cyclopentane as a promoter (Zhang and Lee, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, we should mention the following technologies: degassing of water, distillation homogenization of fuel, mixing of colloidal solutions, foam formation in the food industry, etc. Modern technologies for the insulating materials production [1], desalination of sea water with the help of isobutane hydrate [2][3][4], and obtaining of natural gas hydrate [5,6] for transportation and storage are also based on heat and mass transfer processes in the gas-liquid systems. Generally, formation and existence of gas-to-steam bubbles are accompanied by intensive heat transfer, mass transfer and phase transition processes.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, we should mention the following technologies: degassing of water, distillation of petroleum products, cleaning of surfaces by cavitation, homogenization of fuel, mixing of colloidal solutions, foam formation in the food industry, etc. Modern technologies for the insulating materials production [1], desalination of sea water with the help of isobutane hydrate [2][3][4], and obtaining of natural gas hydrate [5,6] for transportation and storage are also based on heat and mass transfer processes in the gas-liquid systems.…”
Section: Introductionmentioning
confidence: 99%